On not playing Jesus The gendered liturgical theology of presiding - Cones, Bryan (2017)
The male gender of the presider at Eucharist has long been a source of theological reflection both about the Eucharist and the presider's role within it, and about ordination, particularly in relation to the exclusion of women from ordained office across Christian churches. The relatively recent admission of women and gender minorities to orders in some churches troubles the received liturgical and theological traditions in this regard. Drawing on the legacy of the 20th-century North Atlantic liturgical movement and its recovery of the assembly as the 'primary symbol' of the liturgy, this article explores the possible liturgical and theological 'adjustments' proposed by a change in the presumed gender of the presider in relation to the 'primary symbol' of the assembly, and suggests changes in presidential practice that cast into greater relief the liturgical theological significance of gender diversity in the assembly.
Keywords: Eucharist; Assembly; Feminist; Gender; in persona Christi; Liturgy; presiding; Transgender